Profiling Green Property Consumers: A Demographic Analysis of Purchase Intention for Residential Units with Urban Farming Concepts in Makassar City - Zulfikar; Muhammad Novrizal Ramadhan (Business Research and Administration Innovation, 2026)
Although the trend toward environmentally friendly housing (green property) continues to rise, mass marketing strategies often prove ineffective due to highly heterogeneous consumer preferences. This study aims to dissect the demographic characteristics of consumers in Makassar City and analyze how differences in age and educational attainment influence their knowledge, perceptions, attitudes, and purchase intentions regarding housing concepts integrated with urban farming. Utilizing data from 196 respondents, this research applies comparative descriptive analysis and Multi-Group Analysis (MGA) via SEM-PLS. The findings reveal a clear polarization in preferences: the young productive age group (20–29 years old) and highly educated consumers (Bachelor's/Postgraduate degree holders) possess significantly higher ecological literacy and perceived benefits compared to other groups. These results challenge conventional market assumptions and provide actionable insights for property developers to execute precision niche marketing strategies based on demographics in Makassar City.